O projeto de formação educacional do MST e a questão da cultura corporal - Ortiz, Caroline Arnaldo (2018)
In the academic-scientific environment we are currently debating the relationship between Education and Social Movements. It is interesting to verify in this relation the need for an educational formation focused on emancipatory conditions of human life and how this proposal of formation is contemplated in popular education projects, such as the one proposed by the Movement of the Landless Rural Workers (MST). In the present study we highlight the theoretical mediations established between Field Education and the MST when in dialogue with issues involving Body Culture. Thus, we establish as a research problem whether and how the Body Culture is portrayed in texts / documents elaborated by the MST regarding the Field Education. The objective is to characterize the conception of Body Culture linked to the proposal of educational formation of the MST. In order to support our analysis, we appropriate the theoretical contributions of Antonio Gramsci - highlighting the elements that problematize the question of intellectual and culture and the proposal of the Unitary School. The perspective of Body Culture that we adopt is based on epistemological theoretical references of critical Marxist cut, such as brought by the Collective of Authors (1992, 2012). In the analysis of the data collected, we verified that: 1) Body Culture is not portrayed with this term, not even in agreement with the conceptual perspective brought by the Collective of Authors and other authors approached; 2) the conception of Education proposed by the MST is not aligned with the perspective of Body Culture brought in the texts / documents investigated.